The Impact of Interest Rate, Inflation Rate, Time to Maturity and Bond Rating: Indonesia Case - Kusriyanto, Dwi; Nelmida (International Journal of Economics, Business, and Entrepreneurship, 2019)
This study aims to analyze the impact of interest rate, inflation rate, time of maturity, and bond rating on yield to maturity corporate bonds listed on the Indonesia Stock Exchange. The type of data in this study is secondary data. The object of research is all corporate bonds of banking companies listed on the Indonesia Stock Exchange in 2015 - 2017. The sampling technique used is purposive sampling with a total of 70 bonds. This study used multiple regression analysis. Based on the results, shows that the Bank Indonesia interest rate, the maturity period has a positive effect on yield to maturity, while the bond rating does not affect yield to maturity. However, the inflation rate does not affect the yield to maturity. This result can be used by academics, investors and Regulators.